Why do firms delay recalls? The effects of firm type and country of origin on time to recall defective toys in the United States - Tiwari, Sejal (My University, 2019)
This article examines the influence of perceptions of the country of origin of the defective product on time to recall in the context of the U.S. toy industry. Using signalling theory, shareholder/stakeholder perspectives, and drawing on insights from attribution theory, it is suggested that perceptions of low country of origin of the defective product make firms issue quicker recalls. Besides, this effect is more pronounced in publicly traded firms as opposed to privately held firms. Data on 400 toy recalls were obtained from the Consumer Products Safety Commission (CPSC) from 2007 to 2018 to show empirical support for the above. Implications and contributions are discussed.
Presented in absentia on April 27, 2020 at Student Research Day held at MacEwan University in Edmonton, Alberta. Won the Best Student Paper Award in April 2019 at the Administrative Sciences Association of Canada (ASAC) conference held at Brock University in St. Catharines, Ontario.
Keywords: product recall; country of origin; public company